Higher antral follicular count is associated with body weight in peri-pubertal Murrah buffalo heifers - KAVYA, K M; SHARMA, R K; JEROME, A; PHULIA, S K; SINGH, I (The Indian Journal of Animal Sciences, 2019)
AMH had no correlation with AFC and BW, but AFC was correlated with BW in high antral follicular group heifers. Furthermore, this study shows that AMH exhibited a trend with AFC in peri-pubertal buffalo heifers.